2013
DOI: 10.1542/peds.2013-0087
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic DNAemia Heralds CMV-Associated NEC: Case Report, Review, and Rationale for Preemption

Abstract: Human cytomegalovirus (CMV) infection may be acquired in very low birth weight and extremely low birth weight (ELBW) infants from breast milk. The clinical relevance of such infections is uncertain. There is no consensus on whether screening breast milk for CMV, freezing/pasteurizing milk before feeding, or performing virological monitoring on at-risk infants is warranted. We describe an ELBW infant who acquired CMV postnatally from breast milk and developed CMV sepsis syndrome and clinical evidence of necroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 48 publications
1
32
0
Order By: Relevance
“…Most of the studies revealed a possible association between CMV infection and enteritis, 22 17,25,33,36,37,39,40,44,63,65 often with finding of CMV inclusions in histological intestinal samples. It is debatable whether the virus has a role in the pathogenesis of the diseases, either directly or as a secondary super-infection after the acute phase of the enterocolitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the studies revealed a possible association between CMV infection and enteritis, 22 17,25,33,36,37,39,40,44,63,65 often with finding of CMV inclusions in histological intestinal samples. It is debatable whether the virus has a role in the pathogenesis of the diseases, either directly or as a secondary super-infection after the acute phase of the enterocolitis.…”
Section: Discussionmentioning
confidence: 99%
“…Born at 37 WGA, birth weight 2490 g Berardi et al, 2011 (Modena, Italy) 58 Acquired CMV colitis and anaemia in a 2 months old infant with previous surgery for ileum-caecal valve atresia. Born at term, birth weight 3255 g Irizarry et al 2011 (Tampa, FL, USA) 59 Congenitally infected infant with primary CMV enterocolitis, successfully treated with oral valgancyclovir Bar-Meir et al, 2012 (Chicago, IL, USA) 33 CMV NEC in 26 WGA premature infant, birth weight, 864 g. Onset: 29 th day of life Refai et al, 2012 (Brighton, UK) 60 CMV enterocolitis acquired in the 5 th week of life in a term newborn (birth weight 3700 g) Lee et al 2012 (Los Angeles, CA, USA) 61 CMV enterocolitis in a premature newborn (27+4 WGA, birth weight 1130 g, onset at 34 th day of life) Unl soy Aksu et al 2013 (Ankara, Turkey) 53 Description of CMV enteritis and jejunal stricture in a preterm infant Hendriks et 17 Postnatal acquired CMV with septic syndrome and NEC in a 24+5 WGA preterm infant, birth weight 800 g, onset in the 5 th week of life Tran et al, 2013 (Baton Rouge, LA, USA) 63 NEC and CMV in a premature infant (25+1 WGA, birth weight 653 g). Onset at 48 th day of life but history of feeding difficulties after the first week of life Louazon et al, 2014 (Bron Cedex, France) 64 CMV enterocolitis, onset at 10 weeks of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All additional parameters included were self-limiting and there was no impact on neonatal outcome parameters like intracranial hemorrhage, periventricular leucomalacia, retinopathy of prematurity and necrotizing enterocolitis (NEC) 30 . However, a large number of cases and case seriesincluding a case from our department which was observed later on -describe severe illness in VLBW infants including pneumonia requiring artificial ventilation, hepatitis and gastrointestinal involvement, with some infants needing antiviral treatment with (val)ganciclovir 11,26,28,[31][32][33][34][35][36][37] . The onset of viral excretion was detected at day 6 post partum (p.p.)…”
Section: Postnatal Hcmv Infection Of Very Preterm Infants: Neonatal Ementioning
confidence: 99%
“…Cytomegalovirus infection can present as thrombocytopenia, respiratory distress, or can mimic necrotizing enterocolitis. 30 Outbreaks of bloodstream infections can occur in a single nursery or other hospital unit secondary to bacterial contamination of intravenous medication or parenteral nutrition. Clusters of neonates in several different intensive care nurseries have died in recent years due to contamination of total parenteral nutrition with Gram-negative enterobacteria.…”
Section: Nosocomial Infectionsmentioning
confidence: 99%